2020
DOI: 10.1001/jamanetworkopen.2019.21451
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Alcohol-Induced Deaths in the United States, 2000-2016

Abstract: IMPORTANCE Notable increases in mortality from alcohol-induced causes over the past 2 decades in the United States have been reported. However, comprehensive assessments of trends in alcoholinduced mortality by sex, age, race/ethnicity, and social and geographic factors are lacking. OBJECTIVE To examine trends in alcohol-induced mortality rates from 2000 to 2016, comparing results by demographic characteristics including sex, race/ethnicity, age, county-level socioeconomic status, and geographic location. DESI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
100
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 38 publications
2
100
1
1
Order By: Relevance
“…While previous studies have demonstrated a link between excessive alcohol consumption and mortality [53][54][55], we were not able to find any association in Brazil. In Argentina, however, an intriguing association remained significant after adjustment for confounders: those Argentinean provinces with higher prevalence of excessive alcohol consumption presented lower mortality from CVD.…”
Section: Discussioncontrasting
confidence: 98%
“…While previous studies have demonstrated a link between excessive alcohol consumption and mortality [53][54][55], we were not able to find any association in Brazil. In Argentina, however, an intriguing association remained significant after adjustment for confounders: those Argentinean provinces with higher prevalence of excessive alcohol consumption presented lower mortality from CVD.…”
Section: Discussioncontrasting
confidence: 98%
“…Alcohol use disorders (AUD) are complex, moderately heritable (50-60%) [1][2][3][4] , psychiatric disorders associated with heightened morbidity and mortality 5 . An AUD diagnosis includes aspects of physiological dependence, loss of control over drinking, as well as persistent alcohol intake despite physiological, psychological and interpersonal consequences 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…A major strength of the article by Spillane et al 1 is the location of these trends within the broader national landscape, not just in comparison with white individuals as the primary reference group, which is typically the case. In this regard, Spillane et al 1 report that in 2016, the age-standardized rates of alcohol-induced deaths were highest among American Indian and Alaska Native (AIAN) men and women, substantially greater than those among their counterparts in the other major racial/ ethnic populations. Moreover, these rates increased steadily and significantly for both sexes during the 17-year period of observation.…”
mentioning
confidence: 99%
“…This challenge precedes others, including whether the options most likely adopted by AIAN communities offer the best, most well-informed, and most effective treatments 8. As Spillane et al1 note, alcohol-induced deaths are the tip of the iceberg. Alcohol-related deaths-notably suicide, motor vehicle collisions, drowning, and homicide-remain high among AIAN individuals and continue to rise.…”
mentioning
confidence: 99%
See 1 more Smart Citation